Forward Osmosis Process for the Treatment of Wastewater from Textile Industries (Journal of Engineering, 2013)
This paper was aimed to study the efficiency of forward osmosis (FO) process as a new application for the treatment of wastewater from textile effluent and the factors affecting the performance of forward osmosis process.The draw solutions used were magnesium chloride (MgCl2), and aluminum sulphate (Al2 ( SO4)3 .18 H2O), and the feed solutions used were reactive red, and disperse blue dyes.Experimental work were includes operating the forward osmosis process using thin film composite (TFC) membrane as flat sheet for different draw solutions and feed solutions. The operating parameters studied were : draw solutions concentration (10 – 90 g/l), feed solutions concentration (5 – 30 mg/l), draw solutions flow rate (10 – 50 l/hr), feed solutions flow rate (20-60 l/hr), constant pressure and temperature were maintained at 0.5 bar and 30ºC respectively. And includes operating the forward osmosis process using cellulose triacetate (CTA) membrane as flat sheet for different draw solutions and feed solutions. The operating parameters studied were : draw solutions concentration (10 – 90 g/l), and feed solutions concentration (5 – 30 mg/l), constant temperature at 30ºC. It was found that water flux increases with increasing draw solution concentration, and feed solution flow rate and decreases with increasing draw solution flow rate and feed solution concentration for TFC and CTA. It was found MgCl2 given water flux larger than Alum. And also found that reactive red given water flux larger than disperse blue.The experiments also show that CTA membrane gives higher water flux than TFC membrane for forward osmosis operation. The increase in water flux for CTA is about 12.85% than TFC.